UNA TRADUCCIÓN INÉDITA DE MARCIAL - García Romero, Fernando (Myrtia, 1987)
It is study of the manuscript from the middle of the XVIII century which contains the versified translation of a great part of Martial work and the autor of which very probably is the Majorcan Franciscan Antonio Oliver. The work includes a description of metres and their content, an assessment of translation and analysis of metres used in it and the identification of other authors' versions also included in the manuscript.